Serum Enzyme Activity in Murrah Buffalo under Hot-Humid and Cold Seasonal Conditions - Singh, Mohan; Gupta, Barkha; Mittal, Pavan Kumar; Gottam, Govind Sahay; Saini , Bhagat Singh (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
The present study was conducted to evaluate the effect of seasonal variation, specifically the hot-humid (June to September) and cold  period (December to February), on selected serum enzyme activity in adult female Murrah buffalo (n=10). Blood samples were aseptically  collected from the jugular vein, and serum was separated for biochemical analysis. Hepatic enzyme activities were quantified using  an automated Turbo Chem 100 blood biochemistry analyzer. Seasonal variation had no significant effect on serum levels of alanine  aminotransferase (ALT), lactate dehydrogenase (LDH), or alkaline phosphatase (ALP). However, aspartate amino-transferase (AST)  concentrations showed a highly significant decrease (p
Keywords: Hot-humid and cold climate, Murrah buffalo, Seasonal variation, Serum enzymes